Reconstruction of ocean temperature and salinity profiles in the Northern South China Sea using satellite observations - Bo Tang; Bo Tang; Dandan Zhao; Dandan Zhao; Chaoran Cui; Chaoran Cui; Xinhua Zhao (Frontiers in Marine Science, 2022)
Based on historical temperature and salinity (T–S) profiles, the correlation between the sea surface temperature (SST) anomaly, sea surface dynamic height (SSH) anomaly, and temperature profile anomaly is constructed by regression analysis. A three-dimensional temperature field is reconstructed in the northern South China Sea by satellite SST and SSH, with daily temporal and 0.25°×0.25° spatial resolutions. The three-dimensional salinity field is also reconstructed based on the correlation between salinity and temperature. Compared with the observational T–S profiles, the reconstructed T–S field reflects the characteristics and structure and accurately describes the mesoscale variability of the ocean temperature field. The new expanded T–S field can be used as the initial field in numerical models and be assimilated into numerical reanalysis and prediction systems, improving their output.